Prioritizing Market Segmentation Categories for Assessing Online Consumer Behavior in North Cyprus - Sekandari, Elham (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
Consumer behaviour has always been a critical component of marketing activities. Consumers’ behaviour varies based on various aspects of their life. One of the oldest methods used by marketers to understand their consumers’ better, is to divide them into different segments. Technology and the Internet are changing all the traditional ways of doing business and we need to update our knowledge regarding consumer behaviour in this new business environment. Managers also must try to adapt to these changes to stay profitable. Therefore, this study aims to prioritize market segmentation categories when assessing consumers’ online buying behaviour using Analytical Hierarchy Process (AHP). The data were collected through a standard AHP questionnaire from 71 individuals who lived in North Cyprus. Findings demonstrated that age, gender, and marital status are the most critical factors in determining online consumer behaviour. On the other hand, group influence, adaptability, and brand loyalty were found to be the least important factors that can stimulate consumers to shop online. TRNC managers are encouraged to target their consumers based on the categories essential in assessing consumers’ online behaviour since running marketing campaigns and advertising costs money and time for companies. They can also benefit from the results of this study and apply more target-oriented and productive segmentation strategies to enhance their company’s performance.

ÖZ: Tüketici davranışı her zaman pazarlama faaliyetlerinin kritik bir bileşeni olmuştur. Tüketicilerin davranışları hayatlarının çeşitli yönlerine göre değişir. Pazarlamacıların tüketicilerini daha iyi anlamak için kullandıkları en eski yöntemlerden biri, onları farklı segmentlere ayırmaktır. Teknoloji ve İnternet, iş yapmanın tüm geleneksel yollarını değiştiriyor ve bu yeni iş ortamında tüketici davranışlarına ilişkin bilgilerimizi güncellememiz gerekiyor. Yöneticiler ayrıca kârlı kalmak için bu değişikliklere uyum sağlamaya çalışmalıdır. Bu nedenle, bu çalışma, Analitik Hiyerarşi analizi (AHP) kullanarak tüketicilerin çevrimiçi satın alma davranışlarını değerlendirirken pazar bölümlendirme kategorilerine öncelik vermeyi amaçlamaktadır. Veriler, Kuzey Kıbrıs'ta yaşayan 71 kişiden standart bir AHP anketi aracılığıyla toplanmıştır. Bulgular, çevrimiçi tüketici davranışını belirlemede yaş, cinsiyet ve medeni durumun en kritik faktörler olduğunu göstermiştir. Öte yandan, grup etkisi, uyarlanabilirlik ve marka sadakati, tüketicileri çevrimiçi alışveriş yapmaya teşvik edebilecek en az önemli faktörler olarak bulundu. Kuzey Kıbrıs'taki yöneticiler, pazarlama kampanyaları ve reklamlar yürütmek şirketler için para ve zaman gerektirdiğinden, tüketicilerin çevrimiçi davranışlarını değerlendirmede temel olan kategorilere dayalı olarak tüketicilerini hedeflemeye teşvik edilir.
Master of Arts in Marketing Management. Institute of Graduate Studies and Research. Thesis (M.A.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2021. Co-Supervisor: Dr. Iman Aghaei, Supervisor: Prof. Dr. Sami Fethi
Keywords: Business Administration Department; Marketing Management; Marketing onsumer Behaviors--Cyprus, North; Analytic Hierarchy Process AHP, Market Segmentation Categories,Consumer Behaviour, North Cyprus